Reimagining Archetypal Feminist Patterns in Bolu Babalola’s Love in Colour - Sarat Salihu-Abdulakeem; Bamitale Janet Balogun; Khadijat Sanusi (University of Chitral Journal of Linguistics and Literature, 2025)
Traditional mythical narratives emphasise archetypal beliefs about women, particularly as it relates to beauty, and other character traits. These beliefs have been generated from the Greeko-Roman ideas of the goddesses, which have informed various early female narratives and general societal beliefs about women also in African literature. However, recent narrations have been expanded on retelling these stories from the African purview. Therefore, this paper aimed to examine how African writers have recreated archetypal feminist patterns from universal mythical figures in contemporary narratives. To achieve this the archetypal criticism of Jung and Bolen was adopted in a descriptive analysis of selected stories from Bolu Babalola’s Love in Colour: Mythical Tales from around the World Retold. The analysis of ‘Naleli’, ‘Nefertiti’, ‘Osun’ and ‘Siya’ revealed that Babalola’s narratives have transformed culturally known goddesses into contemporary feminist images to retell their stories from a relatable perspective.  In addition, Babalola’s work challenges patriarchal archetypal notions of femininity imbued with weakness and vulnerability by making them symbols of power and strength. The stories emphasise Babalola’s philosophy that the woman reflects the “beauty and beast phenomenon which affirms the diversity of the female gender. The paper concludes that western archetypal abstractions limit the evaluation and interpretation of African archetypal myths, thus, works on such feminine mythical tendencies should reflect the African cultural specificities by adopting tenets, which encompass the ideological purview of the Africans.